Resistance to Marek's disease is controlled by a gene within the B-F region of the chicken major histocompatibility complex in Rous sarcoma regressor or progressor inbred lines of chickens - Plachý, J; Jurajda, V; Benda, V (Folia biologica, 1984)
Rous sarcoma "regressor" chicken lines CB and CB.R1 identical in the B-F region of the B complex (MHC) are susceptible to Marek's disease. On the contrary, the Rous sarcoma "progressor" line CC different in the B-F region from the CB and CB.R1 lines and identical in the B-G region with the CB.R1 line is considerably resistant to MD. The inbred chicken line M is susceptible to MD, although it carries the B21 allele which is generally considered to determine MD resistance. Analysis by means of sera specific for B-F and B-G antigens revealed that the B haplotype of the M line is composed of the B-G region coding for the typical B-G21 antigen and of a different B-F region coding for B-Fx antigen of thus far unknown specificity. Thus genetic resistance to MD is controlled by a gene located within the B-F region of the chicken MHC.
Keywords: Major Histocompatibility Complex; ptačí sarkom; Chickens; Marek Disease; hlavní histokompatibilní komplex; zvířata; Markova nemoc; Sarcoma, Avian; kur domácí; Animals